Traditional Songs of Ìlọrin: Enacting Identities, History, and Cultural Memories - Hakeem Olawale (Yoruba Studies Review)
Ìlọrin is a distinct community and a melting pot where people of diverse ethnic and cultural identities came together to form a settlement in the 17th century. These ethnic groups include Yorùbá, Haúsá, Fúlàní, Núpé, Kànnìké, Kéńbérí, Bàrùbá, and Malians¸ Arabs, among others. However, despite these ethnic and cultural diversities of Ìlọrin and the Fúlàní political hold on it, Yorùbá language is the lingua franca of the community. How these ethnic groups fnd their voices and articulate their historical and cultural identities within this unified framework becomes a source of concern. As a response to this concern, traditional songs of Ìlọrin like dàdàkúàdà, bàlúù, agbè, wákà, kèǹgbè, orin ọlọ́mọ-ọba Ìlọrin, among others sung in Yorùbá language become a site of contestation of ethnic and cultural identities. Te focus of this essay is to analyze Ìlọrin traditional songs as they portray and contest ethnic identities, reconstruct history, and revitalize cultural memories of indigenes. The paper argues that given such a diverse ethnic and cultural origins, performance of Ìlọrin traditional songs become a reminder of family histories, origins, political structure, hegemonic influences, myths, legends, Islamization of Ìlọrin, and a way of ensuring harmony and bridging generational gaps among the various groups in a state that is known as the “State of Harmony”.